Labor Reserves in USSR during 1940s and 1950s: A Socio-Cultural Portrait of Students - S. L. Razinkov; M. B. Larionova; T. A. Zaglodina (Научный диалог)
This article examines key socio-demographic indicators of students enrolled in state labor reserves during the 1940s and 1950s. The research employs mathematical and statistical methods to analyze administrative documentation pertaining to the state labor reserves. A detailed analysis is conducted on various indicators, including gender, age, place of residence, social status, educational level, ethnicity, and health conditions of students in vocational / technical schools and training institutions. The findings reveal the heterogeneity of labor reserve students across specific socio-demographic metrics, as well as the correlation between students’ social profiles and the type of educational institution (school vs. vocational school). Furthermore, the study highlights the dynamic changes in socio-demographic indicators at different stages of the development of the skilled labor training system from the 1940s to the late 1950s. It is noted that these socio-demographic characteristics can be viewed as socio-cultural markers of the informal portrait of labor reserve students, influencing their behavioral practices and mental frameworks. The results of this research can be applied to the study of the evolution of vocational and technical education systems.